Distribution of Dinoflagellate Cysts in Surface Sediments From the Qingdao Coast, the Yellow Sea, China: The Potential Risk of Harmful Algal Blooms - Wang, Zhaohui; Zhang, Yuning; Lei, Mingdan; Ji, Shuanghui; Chen, Jiazhuo; Zheng, Hu; Tang, Yali; Hu, Ren (Frontiers in Marine Science, 2022)
Surface sediments were collected from three sea areas of the Qingdao coast, the Yellow Sea, China, including the inner Jiaozhou Bay, the Laoshan Coast, and the Amphioxus Reserve area in November to December 2017. Dinoflagellate cysts were observed in the sediments, focusing on the distribution of toxic and harmful dinoflagellate cysts. The contents of biogenic elements were analyzed to reveal relationships between cysts and biogenic elements. A total of 32 cyst taxa were identified, including 23 autotrophic and 9 heterotrophic taxa. Cyst concentrations ranged from 83.3 to 346.5 cysts/g D Wt with an average of 210.7 cysts/g D Wt. Generally, cysts of autotrophic dinoflagellates dominated in sediments from the Qingdao coast with the proportions of 41.05%-90.25%. There were no dominated group in cyst assemblages, cysts of Protoperidiniaceae, Suessiales, and Calciodinelloideae showed similar contributions. Cyst assemblages were quite different in Jiaozhou Bay compared to the other two sea areas, with the lowest species richness, diversity and concentration. Notably, seventeen toxic and/or harmful algal bloom (HAB) dinoflagellate cysts were identified in this study, including cysts of the paralytic shellfish poisoning (PSP) producers Alexandrium andersonii, Alexandrium tamarense, Alexandrium minutum, and Gymnodinium catenatum, the yessotoxin (YTX) producers Gonyaulax spinifera, Lingulodinium polyedra and Protoceratium reticulatum, the azaspiracid (AZP) potential producer Azadinium poporum, the ichthyotoxic species Polykrikos geminatus, and eight bloom taxa. Some of these cysts occurred widely and dominantly in this study, such as cysts of Gonyaulax spinifera, Azadinium trinitatum, Scrippsiella acuminata, and Biecheleria halophila, suggesting some potential risk of HABs in the Qingdao coastal area.